Penguatan Akhlak Generasi Alpha melalui Pembelajaran Pendidikan Agama Islam berbasis Teori Humanisme - Ramadhani, Dian Islamiati; Usman, Syahruddin; Mardhati (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2025)
This study examines the strengthening of moral character (akhlak) in Generation Alpha through Islamic Religious Education (PAI) learning based on humanistic theory. Generation Alpha, raised in a digital culture, possesses advantages such as broad access to information, independence, and critical thinking skills. However, they also face significant challenges in moral development due to technological exposure and limited direct social interaction. PAI plays a strategic role as a moral foundation that balances students’ intellectual, spiritual, and emotional intelligence. This research employs a qualitative method with a library research approach, using content analysis of ten journal articles and several relevant academic books. The findings indicate that humanistic theory which emphasizes freedom of thought, respect for human dignity, self-actualization, and child-centered learning is highly relevant to be integrated into PAI instruction. Humanistic approaches such as empathy, open dialogue, worship habituation, storytelling, experiential reflection, and the use of interactive digital media have proven effective in enhancing moral behavior, discipline, empathy, and spiritual intelligence among Generation Alpha. Nonetheless, challenges remain, including cognitively oriented curricula, digital media influence, lack of family role models, and ethical dilemmas in the technological era. This study underscores the importance of adaptive, humanistic, and contextual PAI learning designs as a strategy to develop a morally upright, adaptable, and Islamically grounded Generation Alpha